Tick fever in cattle in the region of Botucatu - SP: A retrospective study of 1986-2007 - Gonçalves, Roberto Calderon [UNESP]; Da Silva, Andreza Amaral [UNESP]; Ferreira, Danilo Otávio Laurenti [UNESP]; Chiacchio, Simone Biagio [UNESP]; Lopes, Raimundo Souza [UNESP]; Borges, Alexandre Secorun [UNESP]; Amorim, Rogério Martins [UNESP] (Universidade Estadual de Londrina, 2011)
A retrospective study of Cattle Tick Fever was made with animals up to one year old, which occurred from 1986-2007 in Botucatu-SP in the influence area of the Veterinary Hospital of the School of Veterinary Medicine and Animal Science - UNESP. There were 232 cases and 57 deaths. The main etiological agent causing the disease on this region is Anaplasma marginale identified as a single agent in 31.5% of the cases. Most of the cases occurred on autumn in mixed-blood animals two to six months old. Predominant clinical signs included apathy, hyporexia or anorexia, dehydration, weight loss and pale mucosa. The high incidence and mortality observed justify prophylactic actions to have the balance between host, agent, vector, and environment, thus avoiding the clinical form of disease and death of livestock herds in the region.
Tristeza parasitária em bovinos na região de Botucatu - SP: estudo retrospectivo de 1986-2007
Keywords: Blood protozoan; Cattle; Tick fever